TYPES OF PROOF AND EVIDENCE IN CRIMINAL PROCEEDINGS DURING THE BUKHARA EMIRATE, KHIVA AND KOKAN KHANATE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article analyzes the specific features of criminal proceedings during the Bukhara Emirate, Khiva Khanate and Kokan Khanate, and provides detailed information on how criminal proceedings were carried out in each khanate, types of evidence and mechanisms of proof. In the Bukhara Emirate, trials were conducted on the basis of religious laws and Sharia, and in the Khanate of Khiva, the khan's decrees and customs were of great importance, and in the Kokan Khanate, the influence of local traditions and social environment was also described. given. The article also discusses the role of the criminal process in the social and cultural life of these times.